Centrifugal breakout reconnection as the electron acceleration mechanism powering the radio magnetospheres of early-type stars. Issue 1 (27th April 2022) - Owocki, S P; Shultz, M E; ud-Doula, A; Chandra, P; Das, B; Leto, P
ABSTRACT: Magnetic B-stars often exhibit circularly polarized radio emission thought to arise from gyrosynchrotron emission by energetic electrons trapped in the circumstellar magnetosphere. Recent empirical analyses show that the onset and strength of the observed radio emission scale with both the magnetic field strength and the stellar rotation rate. This challenges the existing paradigm that the energetic electrons are accelerated in the current sheet between opposite-polarity field lines in the outer regions of magnetized stellar winds, which includes no role for stellar rotation. Building on recent success in explaining a similar rotation-field dependence of H α line emission in terms of a model in which magnetospheric density is regulated by centrifugal breakout (CBO), we examine here the potential role of the associated CBO-driven magnetic reconnection in accelerating the electrons that emit the observed gyrosynchrotron radio. We show in particular that the theoretical scalings for energy production by CBO reconnection match well the empirical trends for observed radio luminosity, with a suitably small, nearly constant conversion efficiency ϵ ≈ 10 −8 . We summarize the distinct advantages of our CBO scalings over previous associations with an electromotive force, and discuss the potential implications of CBO processes for X-rays and other observed characteristics of rotating magnetic B-stars with centrifugal magnetospheres.